Sympathetic innervation of the suprasesamoidean region of the deep digital flexor tendon in the forelimbs of horses. Issue 3 (September 2015) - Beccati, F.; Pepe, M.; Pascucci, L.; Ceccarelli, P.; Chiaradia, E.; Mancini, F.; Mandara, M.T.
Highlights The sympathetic innervation of the normal equine DDFT in the foot was investigated. Most of the sympathetic innervation was in the walls of blood vessels. There is evidence of catecholamine production and functional response in tenocytes. The sympathetic innervation might contribute to an autocrine/paracrine system.